PENGEMBANGAN KETERAMPILAN PENGAJARAN KEWIRAUSAHAAN GURU TK HINGGA SMA MELALUI PELATIHAN PROTOTIPE PRODUK - Muhammad Setiawan Kusmulyono (Jurnal Abdi Insani, 2023)
The implementation of the Merdeka Curriculum through strengthening the Pancasila profile project at the primary and secondary education levels is a valuable breakthrough to strengthen the competence of the nation's students. This implementation needs to be supported by strengthening teacher skills and their ability to manage the learning process. Entrepreneurship turns out to have a positive impact in accommodating the Merdeka Curriculum through creativity and innovation that connect each other. The community service program at ABC Foundation (pseudonym) by strengthening teacher entrepreneurship skills through product prototype training provides evidence that entrepreneurial initiatives can stimulate teacher creativity to create creative products. Through this program, it is hoped that teachers will be inspired to design more creative entrepreneurship-oriented learning models so that they can encourage the realization of the Merdeka Curriculum in a more comprehensive manner.